2011
DOI: 10.1038/oby.2011.94
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure and Heart Rate Effects, Weight Loss and Maintenance During Long‐Term Phentermine Pharmacotherapy for Obesity

Abstract: There is a perception that phentermine pharmacotherapy for obesity increases blood pressure and heart rate (HR), exposing treated patients to increased cardiovascular risk. We collected data from phentermine‐treated (PT) and phentermine‐untreated (P0) patients at a private weight management practice, to examine blood pressure, HR, and weight changes. Records of 300 sequential returning patients were selected who had been treated with a low‐carbohydrate ketogenic diet if their records included complete weight, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 32 publications
(35 reference statements)
0
64
1
Order By: Relevance
“…Additionally, at 52 weeks, systolic and diastolic blood pressure had decreased from baseline in both groups (phentermine: systolic −7.3 mmHg, diastolic −5.4 mmHg; placebo: systolic −8.9 mmHg, diastolic −6.3 mmHg) but the blood pressure difference between groups was not significant despite greater weight loss in the phentermine group. Heart rate changes in the phentermine and placebo groups were also not significantly different at 26 weeks (phentermine −0.9 beats per minute [bpm]; placebo −3.5 bpm) or 52 weeks (phentermine +1.2 bpm; placebo −3.6 bpm) [50].…”
Section: Phentermine Plus Topiramatementioning
confidence: 95%
See 1 more Smart Citation
“…Additionally, at 52 weeks, systolic and diastolic blood pressure had decreased from baseline in both groups (phentermine: systolic −7.3 mmHg, diastolic −5.4 mmHg; placebo: systolic −8.9 mmHg, diastolic −6.3 mmHg) but the blood pressure difference between groups was not significant despite greater weight loss in the phentermine group. Heart rate changes in the phentermine and placebo groups were also not significantly different at 26 weeks (phentermine −0.9 beats per minute [bpm]; placebo −3.5 bpm) or 52 weeks (phentermine +1.2 bpm; placebo −3.6 bpm) [50].…”
Section: Phentermine Plus Topiramatementioning
confidence: 95%
“…Given the increased release of norepinephrine promoted by phentermine, it has the potential to raise blood pressure and heart rate in some patients [48,49]. A recent study by Hendricks et al [50] examined the impact of treatment with phentermine monotherapy and a lowcarbohydrate diet in 300 obese subjects. Weight loss was significantly greater in the phentermine group as compared to placebo beginning at week 1 and continuing through week 104 (P=0.0144).…”
Section: Phentermine Plus Topiramatementioning
confidence: 96%
“…It has recently been reported that abrupt cessation of phentermine in obese subjects on long-term therapy with this psychostimulant did not evoke withdrawal or drug craving. 65 Fixed-dose drug combinations The move by several biotech companies to develop fixed-dose combinations containing approved CNS drugs to treat obesity has a number of drivers. First, it is evident that weight loss can be achieved using currently available antiobesity drugs and they deliver medical benefits to the patient in terms of improved glycaemic control, reduced plasma concentrations of dangerous lipids and reductions in blood pressure.…”
Section: New Cns Approachesmentioning
confidence: 99%
“…Four medications, benzphetamine, diethylpropion, phendimetrazine, and phentermine, are approved for the short-term treatment of obesity (Bray & Ryan, 2012). Although longer term weight loss data on phentermine and related changes in BP and heart rate have been published, it is not approved in the United States for use beyond a few weeks and is not approved in Europe (Hendricks, Greenway, Westman, & Gupta, 2011). In addition, pharmacotherapies for chronic weight management in adults are now available, including orlistat and 2 pharmaceuticals recently approved by the US FDA, lorcaserin and PHEN/TPM ER.…”
Section: Effects Of Intentional Weight Loss On T2dmmentioning
confidence: 99%